Guided Inquiry Learning-Based Literary Learning Evaluation Model as an Instrument for Strengthening Character Values and Student Self-Reflection - Rini Utari; Halimah Halimah; Yeti Mulyati; Sumiyadi Sumiyadi (LP. Ma'arif Janggan Magetan, 2025)
Evaluation of literature learning tends to focus only on cognitive aspects and pays less attention to the potential of literature as a medium for strengthening character and student self-reflection. This study aims to analyze the evaluation model of literature learning based on Guided Inquiry Learning as an instrument for strengthening character values and student self-reflection. This research used a qualitative approach with descriptive methods. The data were collected using the literature study method through reviewing academic sources and analyzed using the theory of Miles, Huberman, and Saldana. The results showed that the Guided Inquiry Learning evaluation model has six main stages, namely orientation, formulating problems, formulating hypotheses, collecting information, testing hypotheses, and concluding. Each learning syntax allows students to construct personal meaning, evaluate the value in the text, and reflect on personal experiences. Evaluation is not only a tool to measure text comprehension, but also a means to build character, increase self-awareness, and strengthen critical thinking skills. The integration of character values in the evaluation process makes this model very relevant in 21st century education.